Impact of fluorine substitution upon the photovoltaic properties of benzothiadiazole-fluorene alternate copolymers1. Issue 57 (25th June 2015) - Cartwright, Luke; Iraqi, Ahmed; Zhang, Yiwei; Wang, Tao; Lidzey, David. G.
<x xml:space="preserve">Abstract</x> The impact of replacing hydrogen with fluorine in efficient moderate-band gap alternating benzothiadiazole-fluorene copolymers is studied. The optical, electrochemical, thermal and photovoltaic properties in bulk heterojunction solar cells are investigated.